(untitled) (Journal of Research Updates in Polymer Science, 2013)
The ter-polymeric hydrogels of vinylacetate (VA), methacrylate (MA) and acrylicacid (AA) were prepared using ethyleneglycoldimethacrylate (EGDMA) as a cross linker and benzoylperoxide (BPO) as an initiator. The effect of acrylic acid concentration on various swelling parameters was studied at different pHs (1.0, 4.0, 5.5, 7.4 and 8.0). A promising relationship was found to exist between media penetration velocity and equilibrium media content of hydrogels at all pH values for various concentration of acrylic acid. The fastest dynamic swelling was observed for the highest concentration of acrylic acid (40 mol % of AA) at pH 8.0. In the kinetic study, during the first hours, a first order kinetics (Fick Model) was observed at pH higher than the value of pKa (4.75) of acrylic acid, the hydrogels exhibiting non-Fickian diffusion mechanism. Whereas, for the acidic media pH, a second order kinetics was observed (Schott Model). Network parameters strongly support the swelling out comes. The relaxations of the ter-polymeric chain were observed after swelling at pH 8.0 via SEM pictures. Thermo gravimetric analysis and differential scanning calorimetric analysis also agree with the above conclusions. Well controlled swelling behavior, network properties, SEM out comings and thermo-gravimetric analysis support the idea to use these hydrogels for targeted drug delivery in the colon part of the digestive tract.